2016
DOI: 10.1016/j.tjog.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia is associated with low placental transthyretin levels

Abstract: The immunohistochemical expression of TTR in the syncytiotrophoblast layer of the placenta decreased significantly after 12 weeks of gestation, paralleling the changing demands of thyroid hormone uptake into the placenta. The reduced TTR expression in the syncytiotrophoblast layer of the preeclamptic placenta might impair thyroid hormone uptake and contribute to the pathophysiology of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Negative controls were set by replacing the primary antibody with phosphate-buffered saline. The digital images were randomly taken at ×200 under light microscope (Olympus BX50, Japan) from four sections of each animal and analyzed by Image pro plus 6.0 (Media Cybemetics Inc., Silver Spring, MA, USA; Zhu et al, 2016). The data were expressed as mean density of positive area.…”
Section: Methodsmentioning
confidence: 99%
“…Negative controls were set by replacing the primary antibody with phosphate-buffered saline. The digital images were randomly taken at ×200 under light microscope (Olympus BX50, Japan) from four sections of each animal and analyzed by Image pro plus 6.0 (Media Cybemetics Inc., Silver Spring, MA, USA; Zhu et al, 2016). The data were expressed as mean density of positive area.…”
Section: Methodsmentioning
confidence: 99%
“…Another groups also found that maternal serum of patients suffering from severe PE has a lower level of TTR which may affect the normal development of the growing fetus 20 22 . In a very recent study, expression of TTR was found to be down regulated in placental tissues from severe PE patients compared to control ones 23 . These findings strongly suggest the fact that PE is associated with reduced levels of TTR.…”
Section: Introductionmentioning
confidence: 91%
“…Immunohistochemical data show that specifically on the syncytiotrophoblast layer, TTR expression peaks in the first trimester and progressively decreases throughout the second and third trimester [9]. Placental TTR expression and uptake might be enhanced by relative hypoxia observed in the first trimester of pregnancy, not coincidentally the moment when the fetus is completely dependent on maternal T4 [10].…”
Section: Maternal Thyroid Hormone Supply To the Fetusmentioning
confidence: 95%
“…Fruscalzo et al showed by immunohistochemistry that in IUGR and severe preeclampsia, there was a much stronger placental TTR signal compared to controls. They hypothesized that placental hypoxia is cause of increased TTR expression in placentas from pregnancies complicated by IUGR and preeclampsia [42], although conflicting data exist [9].…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%